Respuesta :
Simplifying
46 + 4x = -6x + 76
Reorder the terms:
46 + 4x = 76 + -6x
Solving
46 + 4x = 76 + -6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '6x' to each side of the equation.
46 + 4x + 6x = 76 + -6x + 6x
Combine like terms: 4x + 6x = 10x
46 + 10x = 76 + -6x + 6x
Combine like terms: -6x + 6x = 0
46 + 10x = 76 + 0
46 + 10x = 76
Add '-46' to each side of the equation.
46 + -46 + 10x = 76 + -46
Combine like terms: 46 + -46 = 0
0 + 10x = 76 + -46
10x = 76 + -46
Combine like terms: 76 + -46 = 30
10x = 30
Divide each side by '10'.
x = 3
Simplifying
x = 3
46 + 4x = -6x + 76
Reorder the terms:
46 + 4x = 76 + -6x
Solving
46 + 4x = 76 + -6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '6x' to each side of the equation.
46 + 4x + 6x = 76 + -6x + 6x
Combine like terms: 4x + 6x = 10x
46 + 10x = 76 + -6x + 6x
Combine like terms: -6x + 6x = 0
46 + 10x = 76 + 0
46 + 10x = 76
Add '-46' to each side of the equation.
46 + -46 + 10x = 76 + -46
Combine like terms: 46 + -46 = 0
0 + 10x = 76 + -46
10x = 76 + -46
Combine like terms: 76 + -46 = 30
10x = 30
Divide each side by '10'.
x = 3
Simplifying
x = 3